Band Identifying Methods as well as Problems in CR Network - Vinoth, D; Immaculate Mercy, A (International Journal of Computer Sciences and Engineering, 2025)
In present day communication wireless communication has become the most popular communication. Because of this growing demand on wireless applications has put a lot of constraints on the available radio band which is limited and precious. In fixed band assignments there are many frequencies that are not being properly used. So cognitive radio helps us to use these unused frequency bands which are also called as “White Spaces”. This is a unique approach to improve utilization of radio electromagnetic band. In establishing the cognitive radio there are 4 important methods. In this paper we are going to discuss about the first and most important method to implement cognitive radio i.e., “band sensing”. The challenges, issues and techniques that are involved in band sensing will discussed in detail.